The Business of Belonging: Temporary Migration, Chinese New Media and Diasporic Connectivity - Leong, Susan (Intellect, 2015)
The objective of this article is to flesh out the theoretical framework of franchise nation first broached in 2009 as a means of understanding the three intersecting relationships between home nation and diaspora, host nation and diaspora, and home and host nations that surround the migrant condition. The term franchise nation seeks to encapsulate and critique the idea that the core elements of a nation’s culture can, like all franchises products and services, be replicated to order. I contend such a framework to be necessary because current approaches tend to emphasize certain aspects of migration dynamics at the expense of others. In what follows, I explain why this is so and what the franchise nation frameworks add to the analysis of Chinese migration that would otherwise be absent. Instead of dyadic understandings of the relationship between diaspora and nations that explain diasporic connectivity variously as long-distance nationalism, state-led transnationalism or domestic abroad transnationalism, the franchise nation framework is premised on a triadic relationship between diaspora, home and host nation. Starting with the example of Mainland Chinese provisional business migrants (PBMs), the article explains what the franchise nation framework brings to the investigation of the ways in which their everyday connections via Chinese social media inflect their experience of multiple belongings in Australia. The three arms of franchise nation triad in this instance consist of: the business migration policy that connects the Chinese PBMs to Australia; the diaspora engagement strategies with which China reaches out to the Chinese PBM diaspora; and the soft power policy that China employs in its dealings with other nations like Australia. The aim here is to argue for a change in how the study of migration is approached, shifting from a dyadic to a triadic framework.